Polyethylene separator supported thin-film composite forward osmosis membranes for concentrating lithium enriched brine. (1st June 2022) - Sun, Nan; Dou, Pengjia; Zhai, Wentao; He, Hailong; Nghiem, Long D.; Vatanpour, Vahid; Zhang, Yuebiao; Liu, Changkun; He, Tao
Highlights: Post-treatment by benzyl alcohol and hydraulic compaction improves TFC membranes' performance. The highest water flux in open literature was obtained for the PE-supported FO membrane. Superior performance in concentrating lithium enriched brine by FO was observed. A model simulating the FO water flux was successfully developed. Abstract: To extract lithium from salt lake brine involves a process of separation and concentration. After separating lithium from brine, the lithium ion concentration is generally a few hundred mg/L which is far below the required 20-30 g/L (as Li + ) before precipitation as lithium carbonate. The concentration step of a lithium enriched brine is crucial but highly energy-intensive. Spontaneous forward osmosis (FO) technology offers the possibility for concentrating lithium ions with low energy. Because the concentrating process involves both feed and draw solution with very high salinity, it is highly desirable to have a high performance FO membrane with a low structural parameter as well as a high rejection to ions. In this work, thin polyethylene separator supported FO (PE-FO) membranes were prepared and post-treated stepwise with benzyl alcohol (BA) and hydraulic compaction. The effect of the post-treatment on the FO performance was systematically analyzed. Excellent FO performance was achieved: the water flux and reverse salt flux selectivity were 66.3 LMH and 5.25 L/g, respectively, when the active layer is oriented towards the 0.5 M NaCl draw solution with deionized water as the feed. To the best of our knowledge, this FO flux is the highest ever reported in the open literature under similar test conditions. Applied in concentrating lithium enriched brine, the membrane showed superior water flux using saturated MgCl2 as draw solution. A new FO model was established to simulate the water flux during the concentration process with good agreement with the experimental results. The promising results using PE-FO membrane for lithium enrichment opens a new frontier for the potential application of FO membranes. Graphical Abstract: : Image, graphical abstract